KEPASTIAN HUKUM ATAS TINDAK PIDANA PENCEMARAN NAMA BAIK BERDASARKAN KEPUTUSAN BERSAMA TENTANG PEDOMAN IMPLEMENTASI ATAS PASAL TERTENTU DALAM UNDANG-UNDANG INFORMASI DAN TRANSAKSI ELEKTRONIK - Johnson Sahat Maruli Tua Pangaribuan (Fakultas Hukum Universitas Kristen Indonesia, 2023)
Several articles governing acts that are punishable by law in Law Number 11 of 2008 concerning Information and Electronic Transactions as amended by Law number 19 of 2016 concerning Amendments to Law number 11 of 2008 concerning Information and Electronic Transactions, in its implementation, it still creates multiple interpretations and controversy in society, so it is necessary to prepare implementation guidelines for law enforcement officials in carrying out their duties and authorities. Whereas there are several decisions on criminal defamation which in fact convict people who are victims, as in Decision No. 12/Pid.Sus/2019/PN Kmn the defendant had to serve a prison sentence of (1) one month as a result of his statement on Facebook which basically stated that the victim in the a quo case was a perpetrator and the husband of the defendant also admitted in his statement as a witness before the trial that The defendant's husband once had an romantic relationship with the witness-victim which resulted in the Defendant and the Victim's husband being separated. This resulted in a legal vacuum in enforcing the criminal defamation law because what was stated by the Defendant was what it was, and for this decision the Defendant suffered a great loss. many, namely the breakdown of family relationships and also having to serve time in prison. So that the Birth of the Joint Decree is expected to be the starting point for achieving legal objectives that prioritize benefits, certainty, and justice.